2008
DOI: 10.1007/s11882-009-0003-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of leukotrienes in exercise-induced bronchoconstriction

Abstract: Exercise-induced bronchoconstriction (EIB) refers to acute airflow obstruction that is triggered by a period of physical exertion. EIB occurs mainly in individuals with other features of asthma but is especially prominent in a subset of asthmatics with pronounced indirect airway hyperresponsiveness. Leukotrienes (LTs) play a critical role in the pathophysiology of EIB. Asthmatics who are susceptible to EIB have increased levels of cysteinyl LTs (cysLTs [ie, LTs C4, D4, and E4]) in induced sputum and exhaled br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 49 publications
1
34
0
3
Order By: Relevance
“…The rate-limiting step in eicosanoid biosynthesis is the release of unesterified arachidonic acid (AA) from the sn-2 position of membrane phospholipids by phospholipase A 2 (PLA 2 ) (9). Recent work has uncovered 10 mammalian secreted PLA 2 s (sPLA 2 s) that may coordinate eicosanoid synthesis with the well-described cytosolic PLA 2 -a (i.e., cPLA 2 a) (10-12).…”
mentioning
confidence: 99%
“…The rate-limiting step in eicosanoid biosynthesis is the release of unesterified arachidonic acid (AA) from the sn-2 position of membrane phospholipids by phospholipase A 2 (PLA 2 ) (9). Recent work has uncovered 10 mammalian secreted PLA 2 s (sPLA 2 s) that may coordinate eicosanoid synthesis with the well-described cytosolic PLA 2 -a (i.e., cPLA 2 a) (10-12).…”
mentioning
confidence: 99%
“…Evidence suggests that antileukotriene drugs may be particularly effective in exercise -induced bronchoconstriction and aspirin -intolerant asthma. 22 Anti -immunoglobulin E Omalizumab is a humanized anti -immunoglobulin E (IgE) monoclonal antibody. A systematic review of placebo -controlled trials of omalizumab in moderate or severe allergic asthma showed that it reduced exacerbation frequency and facilitated corticosteroid withdrawal.…”
Section: Non -Th2 Inflammation Current Therapies Antifungalmentioning
confidence: 99%
“…The rate-limiting step in eicosanoid biosynthesis is the release of unesterified arachidonic acid (AA) from the sn-2 position of membrane phospholipids by PLA 2 s [21]. Some sPLA 2 s find importance in the development of asthma through the generation of arachidonic acid (AA).…”
Section: Advances In Vascular Medicinementioning
confidence: 99%